FAKTOR YANG MEMPENGARUHI ALTRUISME MASYARAKAT DALAM MENDONORKAN DARAH - Yoga Mukhlana; Arneliwati Arneliwati; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Altruism is a voluntary action taken by a person or group of people to help other without expecting anything in return. Blood donation is the process of delivering blood or blood-based products from one person to another person's. analyze the factors that influence community altruism in donating blood this research alms was ti describe factors that influence community altrusim in the blood transfusion unit of red cross. This research was a descriptive study with cross sectional approch. The sample was 100 respondents taken based on inclusion criteria using purposive sampling technique. The measuring instrument used was a questionnaire. The analysis used is descriptive and the result found 39 respondents, 17-25 years old (late tens), male 62 (62%), with senior hight school 26 respondent (26%), unemployed 30 respondents (30%), moesleem 89 respondents (89%). Effect of the situation on the presence of others 79 (79%), attractiveness 75 (75%), attribution to victim 79 (79%), help if others help 79 (79%), insistence on time 76 (76%), nature of victim needs 72 (72%). influence in individuals on mood 81 (81%), characteristic 76 (76%), gender 67 (67%), residence 68 (68%), parenting 81 (81). This shows that the behavior of community altruism is still high. This research recommends people continue to increase social awareness to help others without expecting anything in return. Keywords: Altruism, Behavior of sosial, Blood donation